Finding the silver lining in the COVID-19 crisis. (May 2022) - Kowalski, Robin M; Carroll, Hailey; Britt, Jordan
Research has confirmed there is a silver lining to many aversive experiences and that negative occurrences can be an opportunity for post-traumatic growth (PTG). To investigate benefit-finding in the COVID-19 crisis, 179 MTurk workers were surveyed. Participants reported dips in satisfaction with work, leisure, fitness, mental health, and finances in the midst of the pandemic, relative to 6 months prior and in the future. Benefit-finding in COVID-19 was significantly related to PTG, coping, gratitude, and mental health. The most common benefits of the crisis included more time with family and friends, slower pace of life, and improvements in physical health.